Perancangan Logo Community Center PKBM Karya Ummat, Cengkareng, Jakarta Barat - Indro Moerdisuroso; Zaitun Y.A Kherid (Universitas Persada Indonesia YAI, 2022)
This community service activity in making a visual identity or logo for the partnerinstitution called Community Learning Center (PKBM) Karya Ummat in Cengkareng,West Jakarta contributed mainly to strengthening related institutions. PKBM which ismanaged by the Karya Ummat Foundation organizes equality education, PAUD, lifeskills, and work skills programs. Established in 2005 and incorporated in 2009, PKBMhas graduated hundreds of participants in the Package B and C equivalence programs,and PAUD participants. However, its visual identity uses the foundation's logo. In fact, tosignify a strong sub-institution, it should develop its own visual identity The activity of logo is carried out through a series of standard stages of corporate identitydesign, especially in the characterstics of community centers. The stages include:collecting information on the characteristics of the institution, literature study,exploration, design, selection, evaluation, revision, application. In this way the series ofdesign processes and their final results are avoided from inconsistency with the client'srequirements. The partner's chosen logo design is applied to letterhead, envelopes,stamps, business cards, participant cards, and neog signs